2019
DOI: 10.3389/fmicb.2019.00198
|View full text |Cite
|
Sign up to set email alerts
|

The Antimicrobial Peptide lin-SB056-1 and Its Dendrimeric Derivative Prevent Pseudomonas aeruginosa Biofilm Formation in Physiologically Relevant Models of Chronic Infections

Abstract: Antimicrobial peptides (AMPs) are promising templates for the development of novel antibiofilm drugs. Despite the large number of studies on screening and optimization of AMPs, only a few of these evaluated the antibiofilm activity in physiologically relevant model systems. Potent in vitro activity of AMPs often does not translate into in vivo effectiveness due to the interference of the host microenvironment with peptide stability/availability. Hence, mimicking the complex environment found in biofilm-associa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
29
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 33 publications
(33 citation statements)
references
References 67 publications
2
29
0
Order By: Relevance
“…Differently from artificial sputum medium, patients' sputum contains host/bacterial components such as cell-derived factors, normal flora, inflammatory mediators, proteases, or peptidases that may exert an additional inhibitory effect on the peptide's activity. Nevertheless, herein, we showed that the combination of lin-SB056-1 and EDTA at sub-active and non-cytotoxic concentrations [16,27] determined a significant reduction in P. aeruginosa load in sputa of PCD chronically infected patients, despite certain differences in the level of reduction among different sputum samples being observed. Such differences are not surprising considering that inter-patient variables (e.g., clinical stage and severity of lung infection, bacterial load, sputum sample composition, and consistency) were not standardized in our experiments, in the attempt to mimic conditions found during the actual antimicrobial therapy.…”
Section: Discussionmentioning
confidence: 55%
See 1 more Smart Citation
“…Differently from artificial sputum medium, patients' sputum contains host/bacterial components such as cell-derived factors, normal flora, inflammatory mediators, proteases, or peptidases that may exert an additional inhibitory effect on the peptide's activity. Nevertheless, herein, we showed that the combination of lin-SB056-1 and EDTA at sub-active and non-cytotoxic concentrations [16,27] determined a significant reduction in P. aeruginosa load in sputa of PCD chronically infected patients, despite certain differences in the level of reduction among different sputum samples being observed. Such differences are not surprising considering that inter-patient variables (e.g., clinical stage and severity of lung infection, bacterial load, sputum sample composition, and consistency) were not standardized in our experiments, in the attempt to mimic conditions found during the actual antimicrobial therapy.…”
Section: Discussionmentioning
confidence: 55%
“…Similar to CF patients, eradication of chronic P. aeruginosa infection in PCD lungs is hardly obtained, and the reduction of bacterial density during chronic colonization or exacerbations is often the aim of the antimicrobial therapy [3]. In previous studies, we have shown that the combination of lin-SB056-1/EDTA possesses antimicrobial activity against P. aeruginosa in artificial sputum medium and prevents P. aeruginosa biofilm formation in an in vivo-like three-dimensional (3D) lung epithelial cell model [16,27]. Despite resembling the airway mucus, artificial sputum media normally behave like Newtonian fluids lacking many of the intramolecular interactions and covalent cross-links that give respiratory secretions their viscoelastic characteristic [28].…”
Section: Discussionmentioning
confidence: 99%
“…Potent in vitro activity of AMPs often does not translate into in vivo effectiveness due to the interference of the host microenvironment with peptide stability/availability. Hence, mimicking the complex environment found in biofilm-associated infections is essential to predicting the clinical potential of novel AMP-based antimicrobials [ 212 ]. The antibiofilm activity of the semisynthetic peptide lin-SB056-1 (KWKIRVRLSA-NH 2 ; Figure 22 ) and its dendrimeric derivative (lin-SB056-1)2-K ([KWKIRVRLSA] 2 -K) against Pseudomonas aeruginosa in an in vivo-like three-dimensional lung epithelial cell model, and an in vitro wound model (consisting of an artificial dermis and blood components at physiological levels) gave rewarding results.…”
Section: Mimicking the Structure Of Ampsmentioning
confidence: 99%
“…The antibiofilm activity of the semisynthetic peptide lin-SB056-1 (KWKIRVRLSA-NH 2 ; Figure 22 ) and its dendrimeric derivative (lin-SB056-1)2-K ([KWKIRVRLSA] 2 -K) against Pseudomonas aeruginosa in an in vivo-like three-dimensional lung epithelial cell model, and an in vitro wound model (consisting of an artificial dermis and blood components at physiological levels) gave rewarding results. [ 212 ]. When alone, Lin-SB056-1 was moderately effective (MIC P.aeruginosa (μM) = 38.5) in reducing P. aeruginosa biofilm formation in 3D lung epithelial cells, but its antibiofilm activity was significantly increased in association with the chelating agent EDTA.…”
Section: Mimicking the Structure Of Ampsmentioning
confidence: 99%
See 1 more Smart Citation